Source of Information of Rukn al-Din Baybars in His Description of the Civil War in the Golden Horde in the late 13th – early 14th centuries » - A.A. Porsin (Золотоордынское обозрение)
The article examines the question of the identity of an anonymous informant of Rukn al-Din Baybars who witnessed both the last Nogai’s battle against Tokhta in 1299–1300 and the battle of the forces of the coalition led by Taz and Tunguz against Chaka in 1300–1301. The author concludes that the Baybars informant was a member of the Golden Horde elite and was close to the Nogai daughter Toguldzhа and her husband Taz. After khan Uzbek came to power and Taz and Tunguz were killed, the Golden Horde embassy was sent in Egypt with gifts including several captured opponents of a new Khan. It is possible, that among them was also a veteran of the war flared in the Golden Horde in the late 13th – early 14th century. Kinship with new Jochid elite that prevented to kill them without the threat of vendetta were the reason for this move. This embassy arrived in Egypt at the end of 1317. And probably after that the author included in “Zubdat al-Fikra” description of the war occured in ulus of Jochi in the late 13th – early 14th centuries.